Assessing the feasibility of a market entry to the French market for a Czech company specialized in joint nutrition - Musil, Marek (2021)
The aim of this thesis was to assess the feasibility of a market entry to the French market for a small family owned business. In order to bring an accurate analysis, the first step was to analyse the industry of dietary supplements. This specific market is composed of a large scale of different products that attract consumers of all age. The Covid-19 pandemic increased considerably revenues of the whole industry that were only on a high level and in general it can be said that the whole industry represents a major component of our economy. A pariticular emphasis was put on the legal framework because the whole industry is heavely influenced by the legislation. Once these fundamentals were discussed, the French market was studied. This market is again considerably regulated by the Frenech authorities and this represents a considerable barrier to entry for the firm. The firm will have to face another challenge as well in the form of specific needs of local customers. In fact, the country of origin of the product is very important for French consumers as was discovered during the research. The company will have to adapt to the local market and it would be advised to set a digital presence in the first step of the expansion as other forms of entry would bring higher risks and less flexibility.